Teaching and Trainings for Professional Learning of English Teachers - Kshetree, Arun Kumar (Butwal Campus Journal, 2023)
Teachers are the change agents of the society and nation and they always have to update themselves with the changes in time, technology and situation. They have to learn all the time. Many teachers are not aware of the teacher learning processes and they are not aware of the various opportunities of teacher learning and professional development. Teacher professional development is not just the product of formal teacher trainings organized by the authorities outside but a product of continuous teaching learning activities of the teachers themselves. The study was conducted by purposively selecting 30 secondary school English teachers of Rupandehi District using a set of questionnaires. This article aims at analysing the teachers' views regarding how teaching and trainings help their professional learning and tries to highlight some of the most common and useful strategies for the process of teacher learning and teachers’ professional development. As most of the strategies presented below do not cost extra fund to apply in the day to day life, the teachers need to use these activities in their day to day life so that they can improve their practices which will ultimately improve the education. It was found that the teachers were not much aware of the fact that they can learn much by teaching and they can develop their practices of teaching through teacher trainings they attended. Not only this, the teachers were found to be not much willing for their professional development as well.